Analisis Pengaruh Kinerja Dosen dan Motivasi Belajar Mahasiswa Terhadap Indeks Prestasi Mahasiswa - Fitantina, Fitantina; Salman, Sudarta (Universitas Muhammadiyah Palembang, 2018)
ABSTRACT Purpose - This study aims to analyze the influence of lecturer's performance on student's learning motivation; to analyze the influence of lecturer's performance and learning motivation to student's GPA; and to analyze the influence of lecturer's performance on GPA through student's learning motivationDesign/methodology - The population used is the students of Muhammadiyah University of Palembang, with the number of samples of 100 students selected using accidental sampling method. Data analysis using path analysis.Findings – The result of the research shows that (1) there is influence of performance and time discipline, course material, lecturing strategy, and lecture evaluation simultaneously to student learning motivation. Partially only lecturing strategy, and lecture evaluation which have positive and significant influence. (2) there are influence of appearance and time discipline, course material, lecturing strategy, lecturing evaluation, and student's motivation to student's GPA. However, only lecture strategies, lecture evaluations, and learning motivations have a positive and significant influence. (3) Indirectly, the strategy of lecturing and evaluation of lectures affect the student's GPA through learning motivation.